Association of the CD14 -260C/T polymorphism with plaque-induced gingivitis depends on the presence of Porphyromonas gingivalis - Bartosova, Michaela; Borilova Linhartova, Petra; Musilova, Kristina; Broukal, Zdenek; Kukletova, Martina; Kukla, Lubomir; Izakovicova Holla, Lydie (International journal of paediatric dentistry, 2022)
BACKGROUND: Plaque-induced gingivitis is the most prevalent periodontal disease associated with pathogenic biofilms. The host immune system responds to pathogens through pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs) and their co-receptor cluster of differentiation 14 (CD14). AIM: This study investigated the association between the functional polymorphism in the CD14 gene and the dental plaque microbiota in children with gingivitis. DESIGN: A total of 590 unrelated children (307 with plaque-induced gingivitis and 283 controls, aged 13-15 years) were enrolled in this case-control study. Dental plaque was processed using a ParoCheck® 20 detection kit. The CD14 -260C/T (rs2569190) polymorphism was determined with the PCR-RFLP method. RESULTS: Gingivitis was detected in 64.2% of boys and 35.8% of girls (P < .001). Children with gingivitis had a significantly higher occurrence of dental caries (P < .001). No significant differences in the CD14 -260C/T allele and genotype distribution among individuals with or without gingivitis in the whole cohort were found. Children with gingivitis and P gingivalis, however, were significantly more frequent carriers of the CT and TT genotypes than children with gingivitis without P gingivalis or healthy controls (P < .05). CONCLUSIONS: The CD14 -260C/T polymorphism acts in cooperation with P gingivalis to trigger plaque-induced gingivitis in Czech children.
Keywords: Male; polymorfismus genetický; Adolescent; Child; dítě; Dental Caries; gingivitis; gingivitida; Case-Control Studies; mužské pohlaví; Polymorphism, Genetic; Gingivitis; mladiství; bacteria; lidé; Porphyromonas gingivalis; ženské pohlaví; studie případů a kontrol; Humans; Lipopolysaccharide Receptors; zubní kaz; lipopolysacharidové receptory; Female; CD14; polymorphism